1950
DOI: 10.3181/00379727-75-18278
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postoperative Adhesions in Rabbits with Streptococcal Metabolites.

Abstract: 18278) LOUIS T. \\-RIGHT, I)A\.ID H. SNTTH, ,\JILTON ROTHMAN, EUGENE T. QUASH, ASD \\*ILLIAM 1. METZGER F r o m thr D c p w t iiictzt o! S u r g e r y , Hn&i?i Hospital, S e w Y o r k Cit?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1954
1954
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…These findings agree with those reported by Wright et al ., who observed a smaller number of adhesions in rabbits when they used streptokinase and streptodornase. [ 34 ] Similar data were reported by Luttwak et al ., in a study of the prevention of adhesions in rats induced by the presence of talcum in the peritoneal cavity. [ 35 ]…”
Section: Discussionsupporting
confidence: 86%
“…These findings agree with those reported by Wright et al ., who observed a smaller number of adhesions in rabbits when they used streptokinase and streptodornase. [ 34 ] Similar data were reported by Luttwak et al ., in a study of the prevention of adhesions in rats induced by the presence of talcum in the peritoneal cavity. [ 35 ]…”
Section: Discussionsupporting
confidence: 86%
“…Intraperitoneal administration of pepsin, trypsin, papain, streptokinase, urokinase, hyaluronidase, fibrinolysin and protoporfirin has been used for the prevention of postoperative adhesions with limited success [3,15,16]. In this study, 50,000 IU/kg streptokinase administered intraperitoneally showed no significant effect for the prevention of postoperative adhesions.…”
Section: Discussionmentioning
confidence: 69%
“…In the late 19th century, agents with potential fibrinolytic capacity, including liquor thiosinamine with sodium salicylate31 and oral phosphorus32, were advocated. Streptokinase and streptodornase were the first agents with proven fibrinolytic properties that were effective in preventing adhesion formation in rabbits and rats33, 34. Although both agents had theoretical value, their efficacy was never proven in humans.…”
Section: Prevention Of Adhesionsmentioning
confidence: 99%